Programmed death ligand 1 (PD-L1) expression influences the immune-tolerogenic microenvironment in antiretroviral therapy-refractory Kaposi's sarcoma: A pilot study. (3rd August 2017) - Mletzko, Salvinia; Pinato, David J.; Robey, Rebecca C.; Dalla Pria, Alessia; Benson, Peter; Imami, Nesrina; Bower, Mark
ABSTRACT: Upregulation of programmed death ligand 1 (PD-L1) is a mechanism of immune escape utilized by a variety of tumors. PD-L1 expression in tumor cells or in the surrounding infiltrate correlates with clinical responsiveness to novel therapies targeting the PD-1/PD-L1 immune checkpoint. In the context of HIV-1 infection, Kaposi's sarcoma (KS) is largely responsive to restoration of immunity following combination antiretroviral therapy (cART), but there is a subset that is not. We hypothesized that this subset of cART-refractory KS may utilize the PD-L1 pathway of immune escape. We found that PD-L1 expressing KS had a denser CD8 + T cell ( p = 0.03) and PD-L1 positive macrophage peritumoral infiltrate ( p = 0.04) to suggest the involvement of PD-L1 in shaping an immune-tolerogenic microenvironment in cART-refractory KS. The presence of PD-L1 expression in association with immune-infiltrating cells provides rationale for the clinical development PD-1/PD-L1-targeted checkpoint inhibitors in cART-refractory KS.